'Anglicanism' and the Origins of the Church of England. (13th August 2014) - McCullough, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> This article aims to provide an introductory historical sketch of the origins of the Church of England as a background for canon law in the present-day Anglican Communion and the Roman Catholic Church. Written by a specialist for non-specialists, it summarises the widely held view among ecclesiastical historians that if the Church of England could ever be said to have had a 'normative' period, it is not to be found in its formative years in the middle decades of the sixteenth century, and that, in particular, the origins of the Church of England and of what we now call 'Anglicanism' are not the same thing.